Equilibrated Atomic Models of Outward-Facing P-glycoprotein and Effect of ATP Binding on Structural Dynamics - Pan, Lurong (Sci Rep, 2015)
P-glycoprotein (Pgp) is an ATP-binding cassette (ABC) transporter that alternates between inward- and outward-facing conformations to capture and force substrates out of cells like a peristaltic pump. The high degree of similarity in outward-facing structures across evolution of ABC transporters allowed construction of a high-confidence outward-facing Pgp atomic model based on crystal structures of outward-facing Sav1866 and inward-facing Pgp. The model adhered to previous experimentally determined secondary- and tertiary- configurations during all-atom molecular dynamics simulations in the presence or absence of MgATP. Three long lasting (>100 ns) meta-stable states were apparent in the presence of MgATP revealing new insights into alternating access. The two ATP-binding pockets are highly asymmetric resulting in differential control of overall structural dynamics and allosteric regulation of the drug-binding pocket. Equilibrated Pgp has a considerably different electrostatic profile compared to Sav1866 that implicates significant kinetic and thermodynamic differences in transport mechanisms.